HLA-A, HLA-B and HLA-C polymorphism in the Slovak population - Kulcsárová, E; Buc, M; Ferencik, S (Folia biologica, 2000)
The occurrence rates of class I HLA alleles were investigated in a sample of the Slovak population by a PCR-SSP method. The frequencies of HLA-A alleles ranged from 0.00 for A*4301 to 0.2798 for A*0201-22; the frequencies of HLA-B alleles ranged from 0.00 for B 4601,B* 4801-3, B*5901,B* 7301, and B* 8101 to 0.1101 for B* 4402-10, and those of HLA-C alleles from 0.00 for Cw*1301 and Cw* 1402-3 to 0.2661 for Cw 0701-10. The occurrence rates of class I HLA alleles established in our study were compared with those in the Czech population. No significant differences were found.
Keywords: elektroforéza v agarovém gelu; HLA-C antigeny; geny MHC třídy I; polymerázová řetězová reakce; Polymerase Chain Reaction; Slovakia; DNA; lidé; Gene Frequency; Genes, MHC Class I; HLA-B antigeny; frekvence genu; Electrophoresis, Agar Gel; HLA-C Antigens; polymorfismus genetický; alely; Alleles; HLA-A Antigens; Slovenská republika; HLA-A antigeny; Polymorphism, Genetic; HLA-B Antigens; Humans